The neighborhood living in our world - Brandwein, Paul Franz 1912-; Bauer, Nancy W.; Mahoney, Erika (San Francisco, [Calif.] Center for the Study of Instruction, 1980)
A social studies text for elementary grades describes the way people live and work in various countries.
Portions of this work previously published in: The social sciences : concepts and values, red.
Keywords: Social sciences